(untitled) (African Disability Rights Yearbook, 2021)
Article 12 of the UN Convention on the Rights of Persons with Disabilities (CRPD) requires state parties to recognise the right to legal capacity of persons with disabilities in its fullest sense. Historically, persons with disabilities have been denied their right to legal capacity. Various states at different times declared persons with psychosocial disabilities, intellectual disabilities, communicative barriers, and in some cases, physical disabilities as legally incapable.1 As a result, the fate of persons with disabilities has been decided either by their relatives or formally appointed guardians. This is the lived reality of persons with intellectual and psychosocial disabilities in many countries including Ethiopia even after the CRPD came into force. This article scrutinises the implications of article 12 of the CRPD for the right to legal capacity of persons with intellectual and psychosocial disabilities in Ethiopia.